Inventario fungico asociado de cultivares de cardo (Cynara cardunculus L.) - Palmero, D.=700 1 Iglesis, C.; Sinobas, J.
(En, Es)
ilus., 24 ref.
Keywords: SEMILLAS; CYNARA CARDUNCULUS; HONGOS; ENCUESTAS; ENFERMEDADES FUNGOSAS; ESPAÑA; CARDO; MICROBIOTA FUNGICA